Optimization and design analysis of 2-kW induction motor shaft by using Finite Element Analysis - Lambert Hotma; Nur Cholis Majid; Marsalyna Marsalyna; Fandy Septian Nugroho; Achmad Ridho Mubarak; Freddy Marpaung (Jurnal POLIMESIN, 2023)
The shaft is a very critical part of a 2-kW induction motor due to its function to support other vital components, such as the rotor, bearing, and casing. Finite Element Analysis (FEA) is used to analyze the shaft model. A meshing convergence test was conducted prior to the optimization. In which a mesh size of 0.5 mm and a tetrahedron shape are selected for the whole simulation to determine critical areas on the electric motor shaft (EMS). In this study, shaft optimization was conducted by using three manners in a sequential process, namely reducing the shaft seat for the rear bearing, modifying the step in front of the rear bearing, and then making the taper from the step in the previous process. This design modification was made to reduce the shaft mass and the maximum equivalent stress. At first optimization, namely replacing the rear bearing and its mount on the shaft, it succeeded in reducing the axle weight by 2,81%. However, the max equivalent stress increased from 30.347 MPa to 54.756 MPa which is located at the intersection of the stepped area, as well as deformation also increased from 0.002434 mm to 0.0026894 mm at the middle shaft. This drawback is overcome by changing the depth of the stepped area and creating a taper. In which the shaft mass can be reduced from 431.07 g to 408.20 g, as well as max equivalent stress is reduced from 54.756 MPa to 28.637 MPa.